Unraveling biochemical properties of cockroach (Periplaneta americana) proteinases with a gel X-ray film contact print method - Hivrale, Vandana K.; Chougule, Nanasaheb P.; Chhabda, Pavan J.; Giri, Ashok P.; Kachole, M. S. (Comparative Biochemistry and Physiology B-Biochemistry & Molecular Biology, 2005)
Eleven proteinase activity bands were detected in American cockroach (Periplaneta americana) gut. These were partially purified and characterized using a gel X-ray film contact print method. Cockroach gut proteinases (CGPs) show activity over a broad range of pH with maximum activity between pH 6 and 10, and optimal activity at 50-70 degrees C. CGPs were partially purified by preparative gel electrophoresis and analyzed using synthetic substrates and inhibitors. Four of the proteases exhibited chymotrypsin-like (C1 to C4) activity and seven trypsin-like (T I to T7) activity. Accuracy of the gel X-ray film contact print method is confirmed by including bovine chymotrypsin in CGP analysis. Inhibition of CGPs with different plant proteinaceous proteinase inhibitors allowed identification of potential CGP inhibitors. Our results imply that presence of several CGP activity bands, and their stability and activity over a broad pH and temperature range might contribute to adaptation of P americana to extreme environmental conditions and the polyphagous nature of the species. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: activity visualization; cockroach; gut enzymes; Periplaneta americana; plant proteinase inhibitors; Proteinases